The Impact of Group Counseling on Reducing Academic Procrastination and Improving Self-Control Among a Sample of High School Students - Abood , Mohammad (Jordan Journal of Educational Sciences, 2018)
This study examined the Rational Emotional Behavioral Therapy (REBT) effectiveness used in group counseling to reduce the level of academic procrastination and improve the self-control of a sample of high school students at Ajloun Governorate. The researcher used an academic procrastination and a self-control scale, Based on the scores of the academic procrastination scales. thirty students were identified as procrastinators; they were randomly assigned into an experimental group and a control group (15 per each). The experimental group received training on (REBT), while the control group didn’t. The result showed that (REBT) was more effective than the no-treatment in reducing academic procrastination in the post and follow-up tests. Moreover, the (REBT) was more effective in improving self-control in the post and in the follow-up tests. In light of the results of the study, the researcher provided several recommendations including the need to employ the (REBT) method to work towards improving self-effectiveness for students in accordance with the positive results for the method revealed by this study